1973
DOI: 10.1136/jnnp.36.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve lesions associated with the carpal tunnel syndrome

Abstract: SUMMARY Electrophysiological studies were performed on median and ulnar nerves in 234 cases of carpal tunnel syndrome. Abnormalities of the ulnar nerve sensory action potential were found in 39.3%0 of cases. The amplitude of the ulnar nerve sensory action potential was related to the amplitude of the median nerve sensory action potential, and to the median nerve motor conduction velocity in the forearm. The findings suggest that in a significant proportion of patients with carpal tunnel syndrome, a more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 13 publications
5
26
1
Order By: Relevance
“…Similar results were found by some authors [10,28,29]. However, there was no significant positive correlation between MDLu and MDLm, which was also noted by Ginanneschi et al [28].…”
Section: Inter-individual Studysupporting
confidence: 80%
See 4 more Smart Citations
“…Similar results were found by some authors [10,28,29]. However, there was no significant positive correlation between MDLu and MDLm, which was also noted by Ginanneschi et al [28].…”
Section: Inter-individual Studysupporting
confidence: 80%
“…Similar results were found by other authors both for sensory parameters of the ulnar nerve [3,10,27] and MDLu [10,28]. However, Azmy et al [30] found a non-significant difference between APSu averages of healthy and affected hands.…”
Section: Inter-individual Studysupporting
confidence: 79%
See 3 more Smart Citations